THE AUDITOR'S REPORT IS IN ACCORDANCE WITH ISA 700 FORMING AN OPINION AND REPORTING ON FINANCIAL STATEMENTS" AND THE REQUIREMENTS OF ISA 705-706 - S.Z. Zaripova; Farruxjon Abdihakimov (Ecominds Press, 2026)
This scientific article examines the main aspects of forming an audit opinion and reporting under the International Standards on Auditing (ISA) framework. The article analyzes the formation of an unmodified opinion under ISA 700 “Forming an Opinion and Reporting on Financial Statements”, the cases of issuing a qualified, adverse opinion and disclaimer of opinion under ISA 705 “Modification of an Audit Opinion”, as well as the importance of ISA 706 “Enhancing Reporting – Matters of Interest and Other Matters”. The specific features of each standard, its practical application, their interrelationships and the information value for users of financial statements are examined in depth. The article also touches on the development and future prospects of the audit opinion.
Keywords: Auditor's Report, ISA 700, ISA 705, ISA 706, Unmodified Report, Modified Report, Highlights, Financial Statements.